Respuesta :

Okay, so -

We have one very important thing here. This little part 6 - (-3). 

Now, it's essential to remember that when we have two negatives like this, we simply draw a line straight down. It becomes a positive! 

So, our question is essentially 5 + 6 + 3 - 8 + 4 - 3 = ? instead of 5 + 6 - (-3) - 8 + 4 - 3! =)

With that in mind, we simply solve left to right. 

11 + 3 - 8 + 4 - 3 = ?

14 - 8  + 4 - 3 = ?

6 + 4 - 3 = ?

10 - 3 = ?

7 is our final answer! =)

Answer:

7

Step-by-step explanation: